2020
DOI: 10.1016/j.jamcollsurg.2020.08.773
|View full text |Cite
|
Sign up to set email alerts
|

Does the Introduction of American College of Surgeons NSQIP Improve Outcomes? A Systematic Review of the Academic Literature

Abstract: Surgery is a central part of healthcare. It is estimated that approximately 11% of the global burden of diseases can be addressed wholly or partly by surgical care. 1 By its very nature, surgery is considered an invasive procedure and therefore carries inherent risks for patients. Based on World Health Organization data, the crude death rate after major surgery is 0.5% to 5%; up to 25% of surgical inpatients experience post-surgery complications, and surgical care accounts for almost half of all adverse events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…This is not surprising considering the higher microbial load of the colon and the generally high rate of surgical site infections associated with colectomies. [12][13][14] Prior studies have demonstrated similar results showing PD + C to be associated with increased risk of infection when compared Note: Values are presented as n (%) unless specified otherwise. Variables with an overall incidence of <1% including outpatient status, transfer status, ventilator dependency, preoperative ascites, history of congestive heart failure, history of renal failure, and preoperative dialysis were omitted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is not surprising considering the higher microbial load of the colon and the generally high rate of surgical site infections associated with colectomies. [12][13][14] Prior studies have demonstrated similar results showing PD + C to be associated with increased risk of infection when compared Note: Values are presented as n (%) unless specified otherwise. Variables with an overall incidence of <1% including outpatient status, transfer status, ventilator dependency, preoperative ascites, history of congestive heart failure, history of renal failure, and preoperative dialysis were omitted.…”
Section: Discussionmentioning
confidence: 99%
“…The ACS‐NSQIP database provides nationally validated, risk‐adjusted data from multiple centers for the purpose of evaluating surgical outcomes 14 . Data are collected by trained surgical clinical reviewers using uniform definitions, sampling methods, and extraction procedures with frequent data audits to ensure accuracy 15 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These databases contain information such as inpatient utilization, access, charges, quality, and outcomes. Patient outcomes have improved since the introduction and widespread use of NSQIP, although using these databases alone will not achieve improvement in surgical quality [ 37 , 38 ]. Access to physiologic data can give researchers more data to help create a standardized EGS transfer pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of NSQIP is to improve the quality and safety of surgical care [ 18 ]. NSQIP is a widely used comprehensive data platform that enables hospitals to continuously track and measure risk-adjusted surgical morbidity and mortality outcome data to inform quality improvements (QI) [ 19 ].…”
Section: Methodsmentioning
confidence: 99%